2020
DOI: 10.3390/cancers12061472
|View full text |Cite
|
Sign up to set email alerts
|

The Expression, Functions and Mechanisms of Circular RNAs in Gynecological Cancers

Abstract: Circular RNAs (circRNAs) are covalently closed, endogenous non-coding RNAs and certain circRNAs are linked to human tumors. Owing to their circular form, circRNAs are protected from degradation by exonucleases, and therefore, they are more stable than linear RNAs. Many circRNAs have been shown to sponge microRNAs, interact with RNA-binding proteins, regulate gene transcription, and be translated into proteins. Mounting evidence suggests that circRNAs are dysregulated in cancer tissues and can mediate various s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 170 publications
(265 reference statements)
2
37
0
Order By: Relevance
“…circRNAs have been reported to participate in the initiation and progression of sepsis, 43 schizophrenia, depression, 44 inflammatory bowel disease, 45 autoimmune diseases, 46 and especially human cancers. 47 , 48 , 49 , 50 , 51 , 52 Therefore, it is reasonable to speculate that they are also potential therapeutic targets. Since our results showed that circRIMS1 was remarkably overexpressed in bladder cancer, siRNA targeting its back-splice junction might represent a novel therapeutic method.…”
Section: Discussionmentioning
confidence: 99%
“…circRNAs have been reported to participate in the initiation and progression of sepsis, 43 schizophrenia, depression, 44 inflammatory bowel disease, 45 autoimmune diseases, 46 and especially human cancers. 47 , 48 , 49 , 50 , 51 , 52 Therefore, it is reasonable to speculate that they are also potential therapeutic targets. Since our results showed that circRIMS1 was remarkably overexpressed in bladder cancer, siRNA targeting its back-splice junction might represent a novel therapeutic method.…”
Section: Discussionmentioning
confidence: 99%
“… 11 circRNAs, which are loop structures without free ends, are highly stable molecules that are resistant to exonucleases (RNase R). 12 Based on biogenesis from different genomic regions, circRNAs can be classified into three main types: exonic circRNAs (EcRNAs), which contain one or more exons derived from alternative splicing and account for over 80% of all known circRNAs; 13 intronic circRNAs (ciRNAs), which only contain introns and may rely on a consensus motif containing a specific base distribution; 14 and exon-intron circRNAs (EIcRNAs), which are formed by both exon and intron elements ( Figure 1 ). 15
Figure 1 Generation, function, transmission, and degradation of circRNAs This process involves several important events.
…”
Section: Characterization Of Circrnasmentioning
confidence: 99%
“… 16 , 17 , 18 , 19 circRNA expression is also modulated by the regulation of circularization, which involves three main hypothetical models: lariat-driven circularization, in which the formation of a lariat structure brings the upstream splice acceptor and downstream donor into close proximity before splicing; intron-pairing-driven circularization, in which the inverted complementary repeat sequences combine into RNA double strands and are subjected to alternative splicing; and RNA binding protein (RBP)-mediated circularization, in which RBPs join the upstream and downstream flanking introns to facilitate pre-mRNA circularization back-splicing ( Figure 1 ). 13 , 20 , 21 , 22 The type of circRNAs generated depends mainly on the elements involved in the three hypothetical models and the splicing pattern.…”
Section: Characterization Of Circrnasmentioning
confidence: 99%
“…The therapy adopted depends on the disease stage, and involves the surgical treatment, radiation therapy, and chemotherapy. circRNAs studies in gynecological tumors have focused mainly on cervical, ovarian, and endometrial cancer [ 121 ], but other genital sphere tumors, such as VSCC, also need to be considered, as reported by Huang et al [ 40 ]. So far, there have been no scientific publications regarding the expression of circRNAs in VSCC.…”
Section: Circrnas and Anogenital Cancersmentioning
confidence: 99%